New technologies in glass - Cutler, Vanessa (London : A&C Black, 2012)
The world of the glass artist is changing. Emerging technology for the cutting, engraving, and printing of glass is opening doors for those who want to work more quickly, more accurately, at larger scales and in multiples, and is stretching the boundaries of innovation. Profiling the latest technology, Vanessa Cutler gives an artist's perspective on new techniques, machinery and software in glass. Using straightforward language, she introduces the digital tools that are becoming an essential part of an artist's toolkit, and describes the application of new technologies, from cutting and engraving machinery to rapid prototyping. These practical essentials are illuminated by the work of contemporary glass artists, who are using these technologies to remarkable effect. New Technologies in Glass is a vital text for any glass artist wishing to expand their toolkit and challenge the possibilities of the medium.
Keywords: Glass craft